Specific Protein Antigen Delivery to Human Langerhans Cells in Intact Skin - Rentzsch, Mareike; Wawrzinek, Robert; Zelle-Rieser, Claudia; Strandt, Helen; Bellmann, Lydia; Fuchsberger, Felix F.; Schulze, Jessica; Busmann, Jil; Rademacher, Juliane; Sigl, Stephan; Del Frari, Barbara; Stoitzner, Patrizia; et al. (Frontiers in Immunology, 2021)
Immune modulating therapies and vaccines are in high demand, not least to the recent global spread of SARS-CoV2. To achieve efficient activation of the immune system, professional antigen presenting cells have proven to be key coordinators of such response. Especially targeted approaches, actively directing antigens to specialised dendritic cells, promise to be more effective and accompanied by reduced payload due to less off-target effects. Although antibody and glycan-based targeting of receptors on dendritic cells have been employed, these are often expensive and time-consuming to manufacture or lack sufficient specificity. Thus, we applied a small-molecule ligand that specifically binds Langerin, a hallmark receptor on Langerhans cells, conjugated to a model protein antigen. Via microneedle injection, this construct was intradermally administered into intact human skin explants, selectively loading Langerhans cells in the epidermis. The ligand-mediated cellular uptake outpaces protein degradation resulting in intact antigen delivery. Due to the pivotal role of Langerhans cells in induction of immune responses, this approach of antigen-targeting of tissue-resident immune cells offers a novel way to deliver highly effective vaccines with minimally invasive administration.